Explainable prediction of chronic renal disease in the Colombian population using neural networks and case-based reasoning - Vásquez-Morales, Gabriel R.; Martínez-Monterrubio, Sergio M.; Moreno-Ger, Pablo; Recio-García, Juan A. (IEEE Access, 2020)
This paper presents a neural network-based classifier to predict whether a person is at risk of developing chronic kidney disease (CKD). The model is trained with the demographic data and medical care information of two population groups: on the one hand, people diagnosed with CKD in Colombia during 2018, and on the other, a sample of people without a diagnosis of this disease. Once the model is trained and evaluation metrics for classification algorithms are applied, the model achieves 95 accuracy in the test data set, making its application for disease prognosis feasible. However, despite the demonstrated efficiency of the neural networks to predict CKD, this machine-learning paradigm is opaque to the expert regarding the explanation of the outcome. Current research on eXplainable AI proposes the use of twin systems, where a black-box machine-learning method is complemented by another white-box method that provides explanations about the predicted values. Case-Based Reasoning (CBR) has proved to be an ideal complement as this paradigm is able to find explanatory cases for an explanation-by-example justification of a neural networks prediction. In this paper, we apply and validate a NN-CBR twin system for the explanation of CKD predictions. As a result of this research, 3,494,516 people were identified as being at risk of developing CKD in Colombia, or 7 of the total population.
Keywords: biological neural networks; diseases; training; data models; artificial intelligence; sociology; chronic kidney disease prediction; neural networks; case-based reasoning; twin systems; explainable AI; support vector machines; random forest; JCR; Scopus